2019
DOI: 10.1021/acs.orglett.9b00579
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Cyclopropyl and Cyclobutyl Ring on Alkyl Iodides through Cobalt-Catalyzed Cross-Coupling

Abstract: A cobalt-catalyzed cross-coupling between alkyl iodides and cyclopropyl, cyclobutyl and alkenyl Grignard reagents is disclosed. The reaction allows the introduction of strained rings on a large panel of primary and secondary alkyl iodides. The catalytic system is simple, non-expensive and the reaction is general, chemoselective and diastereoconvergent. The alkene resulting from the cross-coupling can be transformed to substituted cyclopropanes using a Simmons-Smith reaction. The formation of radical intermedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 70 publications
3
19
0
Order By: Relevance
“…Using the same catalytic system they also showed that α-halogeno βlactams could be functionalised by aryl Grignard reagents (Scheme 44). 128,129 Scheme 44. Functionalisation of α-halogeno β-lactams…”
Section: Scheme 43 Radical Kumada Cross-coupling Of Different Grignard Reagentsmentioning
confidence: 99%
“…Using the same catalytic system they also showed that α-halogeno βlactams could be functionalised by aryl Grignard reagents (Scheme 44). 128,129 Scheme 44. Functionalisation of α-halogeno β-lactams…”
Section: Scheme 43 Radical Kumada Cross-coupling Of Different Grignard Reagentsmentioning
confidence: 99%
“…28 Very recently, the introduction of phenyl bioisosteres consisting of strained cycles such as cyclopropanes or cyclobutanes through cobalt-catalyzed cross-coupling was accomplished. 29 2-Cobalt-catalyzed arylation of alkyl halides 2-1 Arylation of α-bromo glycosides 24 Carbohydrate analogues, such as C-aryl glycosides, are of particular interest in medicinal chemistry due to their enhanced resistance to metabolic processes in comparison to O-glycosides. 30 The introduction of anomeric aryl substituents through metal-catalyzed crosscoupling, on readily accessible α-bromo glycosides, can appear as a straightforward and versatile strategy.…”
Section: -Introductionmentioning
confidence: 99%
“…Based on our previous results on the cross-coupling between alkyl iodides and cyclopropyl Grignard reagents, the use of a cobalt catalyst, Co(acac)2, associated to N,N,N',N'-tetramethylethylenediamine (L = TMEDA), was first selected. 16 Unfortunately, under these conditions, no conversion of the alkyl iodide 5a was observed after 1 h at 0 °C (Table 1, entry 1). To ensure full conversion of 5a, the reaction time was increased to 16 h and the temperature was raised to 50 °C.…”
mentioning
confidence: 99%
“…To identify a catalytic system able to promote the alkylation of a BCP Grignard reagent, the reaction between the primary alkyl iodide 5a and the BCP Grignard reagent, substituted by a t -Bu group at C3, 3a , was first examined. On the basis of our previous results on the cross-coupling between alkyl iodides and cyclopropyl Grignard reagents, the use of a cobalt catalyst, Co­(acac) 2 , associated with N , N , N′ , N′ -tetramethylethylenediamine (L = TMEDA), was first selected . Unfortunately, under these conditions, no conversion of the alkyl iodide 5a was observed after 1 h at 0 °C (Table , entry 1).…”
mentioning
confidence: 99%